Development and Characterization of a Ginger-Boswellic Acid Nanoemulgel for Enhanced Topical Delivery in Osteoarthritis Therapy - Nitin kumar; Dr.Indu Mittal; Raj Kumar Tiwari (Asian Journal of Pharmaceutical Research and Development, 2025)
Osteoarthritis is a prevalent degenerative joint disorder characterized by chronic inflammation and cartilage breakdown, for which conventional oral therapies often suffer from low bioavailability and systemic side effects. In this study, a novel nanoemulgel delivery system was developed to co-deliver boswellic acid (from Boswellia serrata) and 6-gingerol (from Zingiber officinale) topically for localized anti-inflammatory therapy. Nanoemulsions were formulated using oil, surfactant/co-surfactant (Smix), and water, optimized via pseudo-ternary phase diagrams, and then incorporated into a Carbopol 940 gel base. Physicochemical characterization revealed nanosized droplets (145–185 nm) with low polydispersity (PDI 0.18–0.28), negative zeta potential (up to –26.7 mV), skin-compatible pH (5.2–5.8), suitable viscosity, and good spreadability ( 23 g·cm/s for optimal batch). Drug content was high (96–99%) for both active compounds, suggesting efficient encapsulation. In vitro release studies using Franz diffusion cells demonstrated sustained release over 12 hours, with the optimized formulation (G-F3-1.0) showing the best performance. Stability testing under accelerated and long-term conditions confirmed no phase separation, minimal size increase, and maintained drug content. FTIR analysis indicated no significant interaction between the actives and excipients. The developed nanoemulgel offers an effective topical strategy for delivering anti-inflammatory phytoconstituents directly to arthritic tissue, potentially reducing systemic exposure and improving patient compliance. This approach presents promising therapeutic potential for managing chronic joint inflammation in osteoarthritis.